(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Diabetes is major global epidemic with an ever-increasing trend. For diabetic patients hypoglycemia is a fact of life. The gravity of the problem demands that the diabetics must be aware about the symptoms of hypoglycemia as well as its immediate corrective measures to overcome the crisis. But, a substantial proportion of diabetic patients is unaware of all the symptoms of hypoglycemia leading to delayed management. This study was intended to assess the diabetic patients‟ perception about hypoglycemia. Methods: The study was carried out in the Department of Community Medicine, Rajshahi Medical College, Rajshahi over a period of 2 months from April 2018 to May 2018. The diabetic patients in the rural area of Puthia Upazila were the respondents (study population). A total of 107 diabetic patients were consecutively included in the study. A self-administered questionnaire containing the variables of interest for evaluating perception of the respondents about diabetic hypoglycemia was used. Respondents‟ level of knowledge about hypoglycemia was measured using Likert Scale Score. Score „1‟ was assigned for each correct answer and score „0‟ for each wrong answer. As there were more than one question in assessing respondents‟ level of knowledge, combined scores were used to measure respondents‟ perception about hypoglycemia. Result: Over one-third (36.4%) of the respondents was middle aged (40 – 50 years old) and 29% were upper middle aged (50 – 60 years old) with mean age of the respondents being 51.3 years (range: 30-93 years). Approximately 55% were male with male to female ratio being roughly 11:9 More than two-thirds of the respondents took measures to control diabetes and their compliance to treatment was also commendably high (83%). The proportion of controlled diabetics was no less (57%). But their knowledge about common symptoms and causes of hypoglycemia was poor (no more than 25% on an average). The knowledge about measures to be taken to correct hypoglycemia was even poor (no more than 20% on an average). The perception of the significance of symptoms of hypoglycemia and the importance of their correction were disappointingly low (< 10%). Overall half (49.5%) of the respondents had very poor level of knowledge, over one-third (34.6%) had poor knowledge, 13.1% had average knowledge and only 2.8% had good knowledge about symptoms of hypoglycaemia. Conclusion: The study concluded that over two-thirds of the diabetic patients of Puthia Upazilla adopt measures to control diabetes and their compliance to treatment is appreciably high. The proportion of controlled diabetes is also appreciable. But their knowledge about symptoms, causes of hypoglycemia, measures to be taken to correct hypoglycemia and the importance of taking immediate measure to correct hypoglycemia are all inappreciably low. Ibrahim Card Med J 2018; 8 (1&2): 31-38